Quantitative Estimation of Gallic Acid in Triphala Churna by HPTLC - Gouri Kumar Dash (Journal of Global Pharma Technology, 2019)
A simple, reliable and rapid HPTLC method was developed for qquantitative estimation of gallic acid in the methanol extract of Triphala churna. The method was validated as per ICH guidelines for linearity, accuracy, precision, and specificity. Silica gel 60 F254 pre-coated aluminium plates were used as the stationary phase. Toluene: Ethyl acetate: Formic acid: Methanol (12: 9: 4: 0.5) constituted the mobile phase.  Percentage of gallic acid was estimated through densitometry scanning using a TLC Scanner III (Camag, Switzerland) with winCATS software. The amount of gallic acid present in the sample was found to be 0.41 ± 0.08 % w/w with respect to dried plant material. Thus, the developed method can be applied in quantifying the amounts of gallic acid in Triphala churna and results of this work will support in the standardization process of Triphala churna using gallic acid as the biomarker.Keywords: Triphala churna, Methanol extract, HPTLC, Gallic acid.